Analisis Strategi Guru dalam Meningkatkan Kemampuan Berpikir Kritis pada Pembelajaran Tematik Terpadu Siswa Kelas 3 SDN 74 Kota Bengkulu - Elisna, Dea; Aprianti, Celi; Darma Gunawan, Rangga (JPT : Jurnal Pendidikan Tematik, 2024)
A learning strategy is a plan that contains a series of learning activities in the learning process to manage students, manage teachers, manage learning activities and manage the learning environment. Therefore, to achieve educational goals in learning, teachers are expected to have several strategies to improve students' thinking abilities. This research uses descriptive qualitative methods. Data was collected through observation, interviews and documentation. Data is analyzed through Data Reduction, Data Display, Verification. The results of the research show that the teacher's strategy for improving critical thinking skills in integrated thematic learning for class III students at SDN 74 Kota Bengkulu uses lecture, discussion and question and answer strategies. The obstacles faced in improving critical thinking skills come from internal factors such as students who lack clear vision, are slow in grasping material and external factors such as the family and community environment. Efforts made by teachers to improve students' critical thinking skills can come from external factors. interesting learning so that it will motivate students to learn. The conclusion in this research is that the strategies used by teachers at SDN 74 Bengkulu City to improve students' critical thinking skills are still not good. Because teachers do not develop learning strategies. So teachers use expository strategies, namely teacher-centered learning, for example the lecture method. Then there is also some student-centered learning such as discussions, group study, giving assignments.